Plan especial de regeneración urbana para Barrio Cuba - Bulgarelli-Bolaños, José Pablo (Instituto Tecnológico de Costa Rica., 2009)
Currently, the four major quadrants that make up the Gran Area Metropolitana (GAM) in the Central Valley of Costa Rica (San José, Alajuela, Heredia and Cartago), are in a stage of “deterioration and obsolescence” in the metabolic process of its urban structure, in different intensities according to the city. On this stage, occurs in addition the phenomenon of depopulation, that is to say, they are in the period when the urban morphology changes in a negative way the quality, permanence and vitality of these cities. It is necessary to change the current model of urban expansion by an inductive model that prioritizes the recovery of urban centers. According to the National Urban Development Plan (PNDU) this rescue “is directly linked to the repopulation of the cities and the reuse and improvement of its infrastructure and services. Repopulating and densifying existing urban areas in process of deterioration, implies to begin to reverse the trend to grow and build towards the urban periphery, which has caused several problems, including: the increasing of trips per person per day and destruction of the water superficial and groundwater sources, causing flooding due to excess runoff and the destruction of the landscape of our Cordilleras, among others.” This Final Graduation Project (FGP), aims to offer an alternative which helps to implement this change through a Special Urban Regeneration Plan for Barrio Cuba, San José, founded on the principles of strategic planning within the framework of the national urban planning tools (PRUGAM Plan and PUD-MSG) as a reference for future approaches to regeneration in those boroughs in the city of San Jose, with similar urban characteristics. In addition to the Plan, the FGP provides steps to consider in the approach of a methodological procedure as a reference for the development of future plans for urban regeneration.
Tesis (Licenciatura en Arquitectura) Instituto Tecnológico de Costa Rica. Escuela de Arquitectura y Urbanismo, 2009.
Keywords: Urbanismo -- San José (Costa Rica); Planificación urbana; Diseño urbano; Mejoramiento urbano; Recuperación urbana; Arquitectura; Barrios